Padrões de comportamento dos usuários sobre as aberturas para modelos de simulação de desempenho térmico em habitações de interesse social em clima quente e úmido - Oliveira, Andreia Cardoso de (2019)
There are still major differences between the thermal performance of the real building and the simulated building. One reason for this discrepancy is the behavior of the occupants. Thus, this research was developed with the objective of identifying and proposing a model of pattern of use and behavior of the occupants, specifically in relation to openings, in social housing in hot and humid climate, correlating it with the impact on thermal performance of these dwellings. In order to reach the objective, a field research was carried out, in which, in addition to measurements of environmental variables, a questionnaire was applied addressing issues that served as a basis for understanding the users' routines and behavior patterns. The data were collected in two housing estates in João Pessoa, 375 people were interviewed from March 2017 to July 2018. In the statistical analysis three statistical methods were used, descriptive statistics, cross-reference and Cluster analysis, with the help of SPSS v.26 program. The influence of different scenarios of usage patterns and user behavior on the thermal performance of homes was investigated through computer simulation, with the Design Builder v. 6.1.2. The evaluation of thermal performance was based on the composition of two long-term indices: Degrees-hour for Cooling added to the Percentage of hours of discomfort, based on the limits of the adaptive comfort range adopted by De Dear. The results show that the users' behavior can significantly influence the thermal performance of naturally ventilated buildings, confirming the tested hypothesis. Three types of families were identified, whose behavior in relation to openings is strongly related to the time at which residents wake up, that is, to daily routines. It was also possible to observe that the operation of windows and doors can increase the thermal discomfort inside the buildings, however the patterns of use and operation of windows and doors are not only the result of the influence of environmental variables (temperature, relative humidity, speed wind, rain, among others), but also by contextual factors (security, privacy) and cultural factors (family habits, mosquitoes, among others). Users indicated the incentive to open windows and doors upon waking and only to close them when sleeping, which demonstrates that the operation of the openings is linked to a family habit or custom. This pattern can be cultural, as they learned to use the housing in this way with their parents and continued, or even, due to the strong relationship with activities inside and outside the house (intramural). Contextual and cultural factors have had as much influence as environmental factors. Another issue that confirms the influence of contextual and / or cultural factors, refers to users who close the windows when leaving the house or when they go to sleep, even in cases of housing units that have windows with protection bars. That is, although the internal temperature is above the comfort limit, users prefer to close the windows for the feeling of security. In these cases, we found high temperature values, which could be aided by natural ventilation, but users choose to use mechanical ventilation. Thus, it can be concluded that the external temperature is not the determining stimulus for the operation of doors and windows in hot and humid conditions in northeastern Brazil.